Self-representation in literary fandom: Women's leisure reader selfies as postfeminist performance - Dawn S. Opel (Transformative Works and Cultures, 2015)
In social media communities dedicated to women's leisure reading and literary fandom, images of women engaged in the act of reading circulate prominently. These images—created and uploaded to fan sites by the fans themselves—have recurring characteristics: the woman often holds a leather-bound book, wears romanticized, neo-Victorian dress, and has exaggeratedly feminine, sexualized features. These representations are not of actual members of the community but rather fictive, collected, circulated, and commented upon in a communal act of identity construction. This gendered visual representation of the literate self provides a performance of a double movement in postfeminist culture: a broadcasting of discourses that is empowering (participatory digital cultural production around literature) and yet promotes a cultural context for reinforcement of conventional gender norms. To demonstrate this double movement, I utilize a case study of these self-representational fan images, collected over a year on a Facebook group page for fans of 19th-century British literature and filmic adaptations. These images and their circulation are then analyzed via a two-pronged double movement theoretical framework. First, feminist media scholarship helps explain the empowering aspects of the new media creation of the reader selfie. Second, gender performance uncovers how these repeated sexualized images of women readers reentrench conventional, hyperfeminine, and sexualized gender roles. Double movement takes place in contemporary women leisure readers' lives, and the media-led postfeminist cultural movement offers a depoliticized, self-indulgent path toward youth and beauty at the expense of institutional or social change.